Alaadin or jadoo ka cherag - Shaukat hashmi (Ferozsons (Pvt) Limited ; PAKISTAN, 1998)
Alaadin Aur Jadoo Ka Cherag is a magical tale of a young boy's adventure with a mystical lamp, where he encounters a genie and discovers the power of wishes and self-discovery.